Ozone degradation of tetracycline hydrochloride enhanced by magnetic nanofluid composed of Fe3O4 nanoparticles - Li, Mengzhao (Environmental technology, 2025)
Magnetic Fe3O4 nanoparticles were added into the aqueous phase to form nanofluid systems, in which ozone was used for the oxidation of tetracycline hydrochloride (TC) in the solution. The nanomaterials were characterized using SEM, XRD, EDS, and FT-IR. The effects of nanoparticles size, addition ratio, and number of cycles on the process of ozone oxidation of TC were investigated. The results indicated that the addition ratio of nanoparticles have a certain impact on the performance of ozone oxidation. When the addition ratio increased from 0.02% to 0.4%, the removal rate of TC in the solution was improved significantly. Besides, the particle size of nanoparticles showed a greater impact on ozone oxidation. At the nanoscale, Fe3O4 nanoparticles exhibited significant strengthening properties, which is attributed to the construction of nanofluid systems. The removal rate of TC in solution decreased obviously with the increase of nanoparticles size. The Fe3O4 nanoparticles with particle size of 20 nm showed the most significant effect on TC degradation. The recycling experiment showed that magnetic Fe3O4 nanoparticles had stable regeneration performance. For three times of recycling treatment, with a Fe3O4 addition ratio of 0.4%, the removal rate of TC reached 98.7%, 97.21%, and 96%, respectively. Based on the characterization results, the strengthening mechanism was analyzed. The experimental results indicated that construction of nanofluids systems could improve the utilization rate of ozone, and Fe3O4 nanoparticles were reusable and easily recyclable